Redefining status through burqa: Religious transformation and body politics of Indonesia’s woman migrant workers - Rohmaniyah, Inayah; Indiyanto, Agus; Prasojo, Zainuddin; Julaekhah, Julaekhah (AOSIS (pty) Ltd, 2022)
Apart from being commonly understood as a symbol of religious identity, full-face veils (burqa) are also a process through which women redefine their bodies and social status. This article investigates Indonesian women’s commitment to wearing burqa after their work migration in Taiwan and Hong Kong. It focuses on the signification and the redefinition of the body through hijrah(transformation). In-depth interviews conducted with nine Indonesian women migrant workers (WMWs) revealed that this hijrah process characterised by the wearing of the burqa is not always motivated by a religiously radical mindset but more likely by practicalconsiderations aiming to create a sense of security and comfort while working overseas. The burqa is perceived as a symbolic shift in body definition: from being a source of harm, to piety and privilege,paving the way for women to join an emerging elite community,rendering them a new noble and influential social status through socio religious activities. This study recommends that further research on WMWs in the Middle East needs to acquire a more comprehensive picture taking into account its complexity.